Retos pedagógicos en medio de la cuarta revolución industrial (2021)
Understanding that education at the elementary and middle school level is the platform for the reinforcement of logical-mathematical thinking, the exploration of the world in a systemic way and the definition of vocational and occupational trends, the study seeks to examine how teachers of the Basic secondary level of the Pedro Justo Berrío Salesiano Institute (ISPJB) are applying didactic strategies that allow students to develop skills that respond to the challenges of the Fourth Industrial Revolution. An exploratory study was conducted with a qualitative approach. Semi-structured interviews were carried out with teachers, focus groups with the participation of students and teachers, and a documentary analysis through class planners. The investigative exercise made it possible to show that the COVID 19 pandemic accelerated for educational institutions the implementation of new pedagogical initiatives, which allowed connectivity and virtual communication with students. Although the teachers were able to make use of platforms on daily academic sessions, it is appropriate to consider better training in new pedagogical practices related to virtuality. Also, it was observed that teachers apply teaching strategies that help achieve the objectives in the process of teaching and learning for the Fourth Industrial Revolution, as flipped classroom, solving challenges and projects (ABP), learning by doing, among others. However, these should continue to deepen. The management should encourage teacher training so that they reflect about their teaching practices and are at the forefront and constantly updated, in a world immersed in a revolution that generates technological changes rapidly.